Eldercare charities : what drives young Singaporeans to donate to them? - Choo, Mason Shern Min. (2012)
Our research study focuses on the salient factors that affect young Singaporeans’ propensity to donate to eldercare charities. These factors include their empathy towards elderly in need, the levels of transparency and trust they perceive towards the particular charity and also the brand equity of the charity.